A theory of personal budgeting - Simone Galperti (Theoretical Economics, 2019)
Prominent research argues that consumers often use personal budgets to manage self-control problems. This paper analyzes the link between budgeting and self-control problems in consumption-saving decisions. It shows that the use of good-specific budgets depends on the combination of a demand for commitment and the demand for flexibility resulting from uncertainty about intratemporal trade-offs between goods. It explains the subtle mechanism which renders budgets useful commitments, their interaction with minimum-savings rules (another widely-studied form of commitment), and how budgeting depends on the intensity of self-control problems. This theory matches several empirical findings on personal budgeting.
Keywords: D23; D82; D86; D91; E62; G31; 330; Budget; minimum-savings rule; commitment; flexibility; intratemporal trade-off; uncertainty; present bias